Visual Tracking of Numerous Targets via Multi-Bernoulli Filtering of Image Data - Hoseinnezhad, R.; Vo, Ba-Ngu; Vo, Ba Tuong; Suter, D. (Pergamon Press, 2012)
This paper presents a novel Bayesian method to track multiple targets in an image sequence without explicit detection. Our method is formulated based on finite set representation of the multi-target state and the recently developed multi-Bernoulli filter. Experimental results on sport player and cell tracking studies show that our method can automatically track numerous targets, and it outperforms the state-of-the-art in terms of false positive (false alarm) and false negative (missing) rates as detection error measures, and in terms of label switching rate and lost tracks ratio as tracking error measures.